Comparative Evaluation of Maize and Soyabeans as Energy Sources for Broiler Chickens - Onuh, S.O.; Ortserga, D.D.; Okoh, J.J. (Pakistan Journal of Nutrition, 2010)
A total of one hundred and thirty-five (135) unsexed broiler chickens of 5 days of age averaging 72.22±1.11 grams were randomly allocated into 3 dietary treatments designated I, II and III such that full-fat soyabean and maize respectively each predominate (weight for weight) in diets on the one hand while each of the two ingredients were in equal proportions on the other hand. The results at the starter phase show that feed intake and weight gain were not adversely affected (p>0.05) by birds fed all diets. However, the diet which contained the highest level of full-fat soyabean supported insignificantly higher weight gain and efficiency of feed utilization. The results also show that efficiency of feed utilization of birds fed all diets were not significantly affected (p>0.05) while feed cost per unit weight gain of the birds fed the diet where soyabean predominated were significantly better (p<0.05) than birds fed other diets. The results at the finishing phase however show that there were no significant differences (p>0.05) in feed intake, weight gain, efficiency of feed utilization and feed cost per unit weight gain among birds fed diets containing either higher levels of maize or soyabeans. It was observed in the present study that bird fed the diet that contained higher levels of maize had insignificantly (p>0.05) better performance characteristics than those fed the diet that contained higher level of soyabeans. On the basis of the results obtained, it may be recommended that either higher levels of maize or full-fat soyabean may be used as energy sources for broiler starter and finishing broiler chickens without any adverse effect on their performance when prices of each feed ingredients do not differ much.